1997
DOI: 10.1046/j.1469-7580.1997.19020299.x
|View full text |Cite
|
Sign up to set email alerts
|

Lectin binding patterns of porcine oviduct mucosa and endometrium during the oestrous cycle

Abstract: Important functions of the oviduct during reproduction include the provision of an optimal environment for gametes and zygotes and nutrition of the early embryo. These functions are ensured by the secretion of an oviductal fluid which is known to contain organ-specific glycoproteins. Glycoconjugates of the apical glycocalyx are considered to play a major role in cell recognition and interaction processes. In the present investigation, binding patterns of Con A, HPA, LTA, RCA I, UEA I, and WGA were stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
24
1
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 31 publications
9
24
1
2
Order By: Relevance
“…On the one hand, it has been shown that Triticum vulgaris, specific against D-N-acetyl-glucosamine sugar residues, reacts strongly with the oviduct epithelium during the follicular phase (Walter & Bavdek 1997). On the other hand, studies with Helix pomatia (Walter & Bavdek 1997) and Dolichos biflorus lectins, which recognize a-GalNAc residues, have shown that the porcine oviduct expresses this sugar especially during the follicular phase. Therefore, oviductal hexosaminidase might have a role in remodeling the oviduct surface, thus affecting gamete interactions with oviductal cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, it has been shown that Triticum vulgaris, specific against D-N-acetyl-glucosamine sugar residues, reacts strongly with the oviduct epithelium during the follicular phase (Walter & Bavdek 1997). On the other hand, studies with Helix pomatia (Walter & Bavdek 1997) and Dolichos biflorus lectins, which recognize a-GalNAc residues, have shown that the porcine oviduct expresses this sugar especially during the follicular phase. Therefore, oviductal hexosaminidase might have a role in remodeling the oviduct surface, thus affecting gamete interactions with oviductal cells.…”
Section: Discussionmentioning
confidence: 99%
“…In pigs, experiments with lectins show that carbohydrates are differently expressed among regions of the oviduct during the different phases of the estrous cycle (Raychoudhury et al 1993, Walter & Bavdek 1997, Sant'ana et al 2005. Lotus tetragonolobus lectin mainly recognizes a-L-fucose residues, and during the follicular phase its binding sites are only present on epithelial cells of the isthmic segment, the ampulla and infundibulum being unreactive (Walter & Bavdek 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, spermatozoa from the horse and human have also been reported to bind in greater numbers to the isthmus than to the ampulla [56,57]. It is important to realise that regional differences in the expression of glycoconjugates are apparent between segments of the porcine oviduct, and across the different stages of the oestrous cycle, thereby affecting the available binding sites [58]. It seems logical that the difference observed with binding is consistent with the normal physiological functions of the oviduct in these two regions: i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of their putative importance, sialoglycoconjugates have not been studied in horse. Lectins have been successfully used to demonstrate the presence of glycoconjugates in a number of studies including the in situ distribution of glycoconjugates in the mammalian isthmic oviduct, namely in mice (Lee et al, 1983), humans Wu et al, 1993;Kiss et al, 1998), hares (Menghi et al, 1988), rats (Menghi et al, 1989), pigs (Raychoudhury et al, 1993;Walter and Bavdek, 1997), rabbits (Menghi et al, 1995), monkeys (Jones et al, 2001) and horses .…”
mentioning
confidence: 99%